Transformation of identity and contradictions of postideological reality - Kolyadko, Ilya N. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article discusses the key parameters and characteristics of the transformation of the main forms of individual and collective identity in a crisis of the basic foundations of modern culture and under the influence of the contradictions of the modern stage of globalization. The most important modifications of the identification patterns emerging in the culture of postmodernity are revealed that have a significant impact on the processes of sociocultural transformations. The article substantiates the position on the constitutive role of cultural tradition in the unity of its normatively stabilizing and innovative heuristic components in the processes of building identification strategies in transitional societies.
Keywords: identity; post-ideological reality; cultural tradition; fragmentation of identity; crisis of culture